2005
DOI: 10.1002/anie.200500443
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Functionalized Aryl Magnesium Reagents by the Addition of Magnesium Aryl Thiolates and Amides to Arynes

Abstract: Reactive arynes, which are readily generated by the reaction of ortho‐iodoarylsulfonates with iPrMgCl, undergo the smooth addition of various magnesium nucleophiles like magnesium thiolates, selenides, and amides. In all cases the resulting functionalized aryl magnesium species can be trapped by an electrophile leading to highly functionalized aromatic compounds (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(31 citation statements)
references
References 50 publications
0
29
0
2
Order By: Relevance
“…We chose to study tandem S-and N-addition to benzyne in the first instance.Important precedent from Knochel and coworkers had shown that magnesium thiolates undergo efficient addition to benzynes generated from 2-iodophenyl arylsulfonates 4 with i PrMgCl, with the resulting adducts being trapped with simple carbon electrophiles in good yield. [10] Using this chemistry for the initial nucleophilic addition, we then planned to try O-benzoyl N,N-dialkylhydroxylamines as the nitrogen source.T hese electrophilic aminating agents are simple to prepare as stable,c rystalline solids,a nd have recently been shown to have excellent versatility in CÀNb ond formation. [11] Tr eatment of 2-iodophenyl-sulfonate 4 with two equivalents of i PrMgCl in the presence of 4-tert-butyl-benzenethiolate 5 at À78 8 8Ci nT HF,f ollowed by warming of the mixture to 0 8 8C, afforded the expected 2-magnesiated benzothioether 6 (Scheme 2).…”
mentioning
confidence: 99%
“…We chose to study tandem S-and N-addition to benzyne in the first instance.Important precedent from Knochel and coworkers had shown that magnesium thiolates undergo efficient addition to benzynes generated from 2-iodophenyl arylsulfonates 4 with i PrMgCl, with the resulting adducts being trapped with simple carbon electrophiles in good yield. [10] Using this chemistry for the initial nucleophilic addition, we then planned to try O-benzoyl N,N-dialkylhydroxylamines as the nitrogen source.T hese electrophilic aminating agents are simple to prepare as stable,c rystalline solids,a nd have recently been shown to have excellent versatility in CÀNb ond formation. [11] Tr eatment of 2-iodophenyl-sulfonate 4 with two equivalents of i PrMgCl in the presence of 4-tert-butyl-benzenethiolate 5 at À78 8 8Ci nT HF,f ollowed by warming of the mixture to 0 8 8C, afforded the expected 2-magnesiated benzothioether 6 (Scheme 2).…”
mentioning
confidence: 99%
“…Knochel and co-workers developed a facile method for preparing various aryl sulfides with an ortho-substituent, which was accomplished through the thiomagnesiation of arynes to produce an arylmagnesium species that was then trapped with an electrophile ( Figure 14A). 40 Greaney and co-workers recently applied this method in the formal thioamination of arynes ( Figure 14B). 41 Yoshida, Kunai, and co-workers also developed a synthetic method to obtain ortho-stannylaryl sulfides, which was accomplished through the cleavage of the SSn bond in (arylthio)stannane during their reactions with various arynes ( Figure 14C).…”
Section: Transformations Via Arynesmentioning
confidence: 99%
“…Additionally, the low selectivity of metal-iodine exchange reaction on polyiodinated arenes and the possibility for vicinal iodo-lithioarene derivatives to decompose even at low temperatures via a well-known benzyne pathway are other additional challenges. 26,41,42 Recently, we disclosed efficient and practical two methods for the synthesis of 1,2,3-triiodoarenes over two-step protocols from aromatic amines or aromatic carboxylic acids respectively. 20,43 Remarkably, 1,2,3-triiodoarenes are found to be crystalline and bench stable solids compare to other polyiodoarene compounds.…”
Section: Introductionmentioning
confidence: 99%